2012
DOI: 10.1248/bpb.35.265
|View full text |Cite
|
Sign up to set email alerts
|

Genotype Distributions and Allele Frequencies of Possible Major Depressive Disorder-Associated Single Nucleotide Polymorphisms, Cyclic Adenosine Monophosphate Response Element Binding Protein 1 rs4675690 and Piccolo rs2522833, in a Japanese Population

Abstract: It is known that the onset of major depressive disorder (MDD) would be associated with genetic factors. To investigate the susceptibility to psychiatric disorders, e.g. MDD, schizophrenia etc., it is necessary to compare the genetic differences of objective polymorphisms between in patients and in relative contol subjects. Recently, an increasing number of studies focused on the role of cyclic adenosine monophosphate response element binding protein 1 (CREB1) and Piccolo (PCLO) on MDD. However, there was no re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“… 6 In the Japanese population, the frequency of carriers of the rs2522833 C-allele (that is, those with an A/C or a C/C genotype) is larger than that of A/A individuals. 7 A series of studies by Woudstra et al demonstrated that the PCLO C-allele increases the vulnerability of an individual to develop MDD by regulating regional brain function that responds to salient stimulation and processes negative information. 8 , 9 Ryan et al 10 recently reported that PCLO rs2522833 was also associated with the volume of the gray matter (GM), and to a lesser extent with hippocampal volume and white matter lesions in patients with late-life MDD.…”
Section: Introductionmentioning
confidence: 99%
“… 6 In the Japanese population, the frequency of carriers of the rs2522833 C-allele (that is, those with an A/C or a C/C genotype) is larger than that of A/A individuals. 7 A series of studies by Woudstra et al demonstrated that the PCLO C-allele increases the vulnerability of an individual to develop MDD by regulating regional brain function that responds to salient stimulation and processes negative information. 8 , 9 Ryan et al 10 recently reported that PCLO rs2522833 was also associated with the volume of the gray matter (GM), and to a lesser extent with hippocampal volume and white matter lesions in patients with late-life MDD.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the CREB1 rs4675690 polymorphism was determined by allele-specific PCR as previously reported 21) ( Table 3). In brief, genomic DNA (100 ng) was amplified in a PCR buffer containing dNTP mixture (200 µM), forward primer (1 µM), allele-specific reverse primer (1 µM), 1.5 mM MgCl 2 , and HotStar Taq plus DNA polymerase (1.25 units).…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Genome-wide association studies (GWASs) are important tools for elucidating the mechanisms underlying schizophrenia, including the formation of diseases. The dopamine hypothesis, the current leading theory of the pathogenesis of schizophrenia [ 4 , 5 ], is supported by genetic studies indicating that single nucleotide variations (SNVs) related to dopaminergic transmission, such as DRD2 [ 6 ], COMT [ 7 ], DISC1 [ 8 ], and PCLO [ 9 , 10 , 11 ], are associated with a higher risk of schizophrenia [ 5 , 12 ]. The GWAS conducted by the Schizophrenia Working Group of the Psychiatric Genomics Consortium has had a notable impact on the study of schizophrenia [ 13 ].…”
Section: Introductionmentioning
confidence: 99%